Production of nitric oxide by blood monocytes in patients with drug-sensitive and drug-resistance pulmonary tuberculosis - A. K. Strelis; V. V. Novitsky; O. I. Ourazova; N. A. Zemlyanaya; O. V. Voronkova; O. V. Filinyuk; N. P. Pirogova; V. A. Serebryakova; L. N. Bouinova; I. E. Yesimova (Бюллетень сибирской медицины)
Nitric oxide NO• production by blood monocytes was studied in 53 patients with drug-sensitive pulmonary tuberculosis (TB) and 50 patients with multidrug resistance (MDR) TB before and during the anti-tuberculosis therapy. Levels of NO• production were determined using the Griess's reactant. Increased levels of NO• secretion were observed before the treatment and after the intensive phase of therapy of drug-sensitive TB. However, it decreased after the full course of the anti-tuberculosis therapy. At the MDR TB the NO• production by monocytes was reduced before and after the intensive phase of treatment and increased after the end of the full course of therapy.